Characterization of Coelomic Fluid Cell Types in the Starfish Marthasterias glacialis Using a Flow Cytometry/Imaging Combined Approach - Andrade, Claúdia; Oliveira, Bárbara; Guatelli, Silvia; Martinez, Pedro; Simões, Beatriz; Bispo, Claúdia; Ferrario, Cinzia; Bonasoro, Francesco; Rino, José; Sugni, Michela; Gardner, Rui; Zilhão, Rita; et al. (Frontiers in Immunology, 2021)
Coelomocytes is a generic name for a collection of cellular morphotypes, present in many coelomate animals, and that are highly variable among echinoderm classes. The roles attributed to the major types of the free circulating cells present in the coelomic fluid of echinoderms include immune response, phagocytic digestion and clotting. The main aim of the present study is the characterization of coelomocytes present in the coelomic fluid of Marthasterias glacialis (class Asteroidea) through the combined use of flow cytometry (FC) and fluorescence plus transmission electron microscopy. Two coelomocyte populations (here named P1 and P2) were identified by flow cytometry and subsequently studied in terms of abundance, morphology, ultrastructure, cell viability and cell cycle profiles. Ultrastructurally, P2 diploid cells showed two main morphotypes, similar to phagocytes and vertebrate thrombocytes, whereas the small P1 cellular population was characterized by a low mitotic activity, relatively undifferentiated cytotype and a high nucleus/cytoplasm ratio. In the present study we cannot exclude the presence of haploid P1 cells resembling the stem-cell types present in other animals. P1 and P2 cells differ also in cell viability and cell cycle profiles. Additionally, we report the presence of two other morphotypes that were only detected by fluorescence microscopy and a third additional one revealed by a combined microscopy/FC approach.